The effect of motorized vehicle emission toward lead accumulation and rice productivity alongside the uphill of Paguyangan main road, Brebes Regency - Arif Yulianto; A H Syaeful Anwar; S Sakhidin; Okti Herliana (Journal of Degraded and Mining Lands Management, 2019)
This study that was carried out in paddy fields on Paguyangan Highway in Paguyangan Village, Paguyangan District, Brebes Regency, was aimed to find out the effect of the road incline position, the distance between road and rice field toward the lead content and rice productivity. The study used a survey method namely purposive random sampling with two factors. The first factor was the incline position consisting of three slope levels, i.e. the beginning of the ramp (T1) with an altitude of 300 m above sea level (m asl), and a slope of 3.4º, the mid ramps (T2) with an altitude of 315 m asl and slope of 15.84º, and the end of the ramp (T3) with an altitude of 330 m asl and a slope of 8.7º. The second factor was the distance of sampling points from road i.e. 15 m (J1), 35 m (J2) and 55 m (J3). The measured variables were lead contents in rice and soil, as well as, the yield of rice. The results showed that the difference in incline position and distance between roads toward plants did not significantly affect lead content in rice, lead content the soil, and rice productivity on paddy fields around Paguyangan Highway, Paguyangan Village, Brebes Regency, although the lead contents in rice and in the soils were above the specified threshold.